Automated Photovoltaic Irrigation and Monitoring System with Internet of Things for Fertigation System - Bukhari, Muhammad Aliff Bazli; Abdullah, Mohd Noor (Evolution in Electrical and Electronic Engineering, 2022)
Agriculture is the main source for Malaysians, especially in rural areas to generate income for daily living. However, some plants need very careful care to get more efficient results and need more workers to take care of them. The main objective of this project is to develop an automatic system to irrigate the plant using a photovoltaic (PV) power system and monitoring capability as well as the prototype of the project system. NodeMCU is being selected as a microcontroller for controlling the whole system while the soil moisture sensor and ultrasonic sensor are used to control the water pump to operate and monitor the level of water in the tank. The additional ESP-32 CAM in this system project also helps the user can monitor the plant physically in live streaming. The finding of this project is shown in the functionality of the automated system and the monitoring system with the internet of things tested. As a result of this finding, the system is able to operate automatically in irrigating the plant as well as successful in connecting the user with the IoT base to monitor the system and the plant physically. In the future, the water level in the tank can be automatically filled to ensure that the tank always has sufficient water to irrigate the plant.